2009
DOI: 10.1038/mt.2009.53
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Chaperone N-butyldeoxynojirimycin Enhances Enzyme Replacement Therapy in Pompe Disease Fibroblasts

Abstract: In spite of the progress in the treatment of lysosomal storage diseases (LSDs), in some of these disorders the available therapies show limited efficacy and a need exists to identify novel therapeutic strategies. We studied the combination of enzyme replacement and enzyme enhancement by pharmacological chaperones in Pompe disease (PD), a metabolic myopathy caused by the deficiency of the lysosomal acid α-glucosidase. We showed that coincubation of Pompe fibroblasts with recombinant human α-glucosidase and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 46 publications
2
125
1
Order By: Relevance
“…These observations highlighted the fact that the nature and location of amino acid substitutions play a determinant role in the response of GAA variants to pharmacological chaperones. Furthermore, a synergistic effect of N-butyl-DNJ and rhGAA was observed in Pompe disease fibroblasts, resulting in a higher enzymatic correction due to an improved enzyme maturation and delivery to the lysosome (65). These results have important clinical implications, because the association of ERT and chaperonemediated therapy may be particularly useful in patients poorly responding to therapy.…”
Section: Pharmacological Chaperonesmentioning
confidence: 84%
“…These observations highlighted the fact that the nature and location of amino acid substitutions play a determinant role in the response of GAA variants to pharmacological chaperones. Furthermore, a synergistic effect of N-butyl-DNJ and rhGAA was observed in Pompe disease fibroblasts, resulting in a higher enzymatic correction due to an improved enzyme maturation and delivery to the lysosome (65). These results have important clinical implications, because the association of ERT and chaperonemediated therapy may be particularly useful in patients poorly responding to therapy.…”
Section: Pharmacological Chaperonesmentioning
confidence: 84%
“…13,14 However, mutant GAAs responsive to these imino sugars are restricted to a limited group with specific amino acid substitutions, and the enhancing effects of the imino sugars available are not so strong. [13][14][15] For further improvement of pharmacological chaperone therapy for Pompe disease, detailed information on mutant GAAs responsive to small molecules is required.…”
Section: Introductionmentioning
confidence: 99%
“…Although pharmacological chaperone therapy (PCT) has been developed as a strategy to rescue mutant enzymes from degradation, recent studies showed that chaperones are also able to enhance physical stability and potentiate the therapeutic action of the enzymes used for ERT (40)(41)(42)(43). These studies, performed in cell systems and in the animal models of Pompe and Fabry disease, suggested a major change in the use of PCT.…”
Section: Combination Of Chaperones and Ertmentioning
confidence: 99%